THE EFFECT OF PROCESSING TIME ON THE PROXIMATE AND PHYTOCHEMICAL COMPOSITION OF - CHIKA C, UNEGBU; S.C, NJOKU; OBINNA, AJAH; VICTOR, CHIMA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Proximate and phytochemical analysis of the seeds of Brachystegia eurycoma were carried out on the boiled and soaked samples at different time interval to ascertain which of the treatment method that is more conserved. The phytochemical and proximate analysis were carried out using standard method described by Harbone (1973) and A.O.A.C. (2005) There is significant differences (P<0.05) between the samples and the control in the moisture, ash, fibre, protein, fat and carbohydrate content. The moisture content of the seeds increases as treatment time increases, the moisture value ranges between 9.72±0.01 – 13.8±0.01%. The control has the highest value in the ash, fat, fibre and protein content. The phytochemical result showed that there is a significant difference between the treated samples and the control in the alkaloid determination with the value ranging from 4.38±0.06 – 7.41±0.01%, flavonoid content of the samples decreases as the treatment time increases @0.05 level of significance. The flavonoid value of all the samples ranges from 0.76±0.01 – 2.28±0.01%. The tannin and saponin value shows significant different (P<0.05) between the control and the treated samples. The result indicated that processing has effect on the nutritional composition, and thus, shorter time frame should be adopted for treatment.